If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(b + -1x) = a(x + -2) (b * 5 + -1x * 5) = a(x + -2) (5b + -5x) = a(x + -2) Reorder the terms: 5b + -5x = a(-2 + x) 5b + -5x = (-2 * a + x * a) 5b + -5x = (-2a + ax) Solving 5b + -5x = -2a + ax Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '5x' to each side of the equation. 5b + -5x + 5x = -2a + ax + 5x Combine like terms: -5x + 5x = 0 5b + 0 = -2a + ax + 5x 5b = -2a + ax + 5x Divide each side by '5'. b = -0.4a + 0.2ax + x Simplifying b = -0.4a + 0.2ax + x
| -2*2n+3=8 | | 4*x-2-12=0 | | 7y-2y-84=2y-2y+61 | | (3a+b)-bx=a(x-2) | | N^3-6n^2-4n+24=0 | | 9x-(4x-10)=50 | | 27r^3+125=0 | | 16z^2-40z+25=0 | | ((100x^2)/16)-(4y/49) | | 156.25+5.75x=7x | | 32-12y+y^2=0 | | -64b^2+0z+25=0 | | 25-64b^2=0 | | 13/7(1/2) | | 13/1 | | 8z^2-88z+240=0 | | 7+8v=6+8v | | 3in+X=11in | | X+3in=11in | | 2(x+1)-3(x-1)=5-x | | 2(x+1)-3(x-1)=5-1 | | 3*ln(e)= | | 9(x-10)=-27 | | .20=x^2/85-x | | 5x^3+33x^2-12x+14=0 | | -5/6-(-8/9) | | -7(v+6)=-5v-28 | | (-7/8)^3 | | (x-10)(x+2)=25 | | -10-4x=4x-2 | | 7x^2+2=15 | | 8(y+3)-10y=0 |